2020
DOI: 10.1111/cxo.13060
|View full text |Cite
|
Sign up to set email alerts
|

Posterior segment conditions associated with myopia and high myopia

Abstract: Myopia, and especially high myopia, is associated with a number of posterior segment changes that are considered to be mostly a consequence of the increased axial elongation. This can result in mechanical strain, attendant vascular changes, stretching and thinning of tissues, and atrophy/deformation of tissues in later or more advanced stages. Such myopiarelated changes are observed as changes and/or abnormalities in the vitreous, choroid, retina and peripheral retina, sclera and/or optic disc. Although many o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 116 publications
(349 reference statements)
1
5
0
Order By: Relevance
“…When considering only those patients in our study younger than 12 years at the time of examination, only 5% (2/37) presented with a posterior staphyloma, 11% (4/37) presented with peripapillary atrophy and 38% (14/37) presented with diffuse chorioretinal atrophy. These findings are significantly different from those of studies in older patients, such as that by Gozum et al, which showed posterior staphylomas in 23.6% of cases and peripapillary crescents in 66.5% [71], results that agree with those of Jagadeesh et al (2020), who observed a higher prevalence of myopic funduscopic changes in older patients [72]. These findings are consistent with the constant corneal remodeling and thinning performed by these MMPs.…”
Section: Other Genessupporting
confidence: 44%
“…When considering only those patients in our study younger than 12 years at the time of examination, only 5% (2/37) presented with a posterior staphyloma, 11% (4/37) presented with peripapillary atrophy and 38% (14/37) presented with diffuse chorioretinal atrophy. These findings are significantly different from those of studies in older patients, such as that by Gozum et al, which showed posterior staphylomas in 23.6% of cases and peripapillary crescents in 66.5% [71], results that agree with those of Jagadeesh et al (2020), who observed a higher prevalence of myopic funduscopic changes in older patients [72]. These findings are consistent with the constant corneal remodeling and thinning performed by these MMPs.…”
Section: Other Genessupporting
confidence: 44%
“…Axial elongation is generally the result of structural changes in the posterior segment. Nonetheless, the mechanical stretching caused by axial elongation is usually accompanied by a reduction in oxygen consumption, eventually affecting the structure of the posterior segment [24][25] , such as the retina [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Emmetropes had non‐cycloplegic subjective spherical equivalent refractions (SER) between Plano and +0.50 D, and myopes had non‐cycloplegic SER between −0.75 D and −6.00 D. Subjective refraction included monocular subjective refraction using best vision sphere—maximum plus to maximum visual acuity; cylindrical power; and axis refinement using the Jackson cross‐cylinder and binocular balancing using the monocular fogging balance (modified Humphriss) method. As high myopia (≤−6.00 D) carries a risk of pathological changes such as myopic maculopathy and retinal detachment (reviewed by Jagadeesh et al 31 ) and can affect accommodation measurements, individuals with high myopia were excluded. People with anisometropia >1.50 D and/or cylinder >1.50 D, or with a past or current history of myopia control treatment, for example orthokeratology and multifocal lenses, were also excluded.…”
Section: Methodsmentioning
confidence: 99%